Deformation of crystalline materials part 2 (Strength and Deformation of Solids, 1975)
This video present single crystals of zinc in different orientations are deformed in a tensile testing machine. An animated sequence of plastic deformation is related to the basal slip plane of a hexagonal close-packed structure. Illustrates why the close-packed planes are more easily deformed than planes that are not close-packed. A polycrystalline specimen is deformed as well, and the resultant slip bands are shown in a micrographic view of the sample. From the Strength and Deformation of Solids series.